206 Effects of a Direct Fed Microbial and/or an Enzymatically Hydrolyzed Yeast Product Fed to Beef Steers Provided Ractopamine Hydrochloride 28 d Before Harvest During Summer Months in the Northern Plains. (12th April 2022) - Gubbels, Erin; Rusche, Warren C; Rehberger, Tom G; Block, Elliot; Smith, Zachary K
Abstract: This research determined the influence a direct fed microbial (DFM) and/or enzymatically hydrolyzed yeast (EHY) product (Arm & Hammer Animal and Food Production, Princeton, NJ) have on heat stress measures in beef steers administered ractopamine hydrochloride (RH; 300 mg/steer·d -1 ) the final 28-d on feed, during summer months in the Northern Plains (NP). At weaning, single-sourced steers (n = 256; initial BW = 246 ± 1.7 kg; n = 64 steers/treatment; 8 steers/pen) were blocked by location in a 2×2 factorial arrangement of DFM (Certillus CP B1801 dry; Bacillus subtilis, Lactobacillus plantarum ; 28 g/steer·d -1 ) and EHY (Celmanax; 18 g/steer·d -1 ). The final diet provided 1.44 Mcal/kg of NEg and 30 g/907kg of monensin sodium. Temperature-humidity index (THI) was calculated from: 0.81 × ambient temperature + [relative humidity × (ambient temperature - 14.40)] + 46.40. On d 1 and 2 and d 21 and 22 on RH, respiration rate (RR) and panting scores (PS) were determined before and after AM and PM feedings (0700h, 1100h, 1400h, 1700h). RR (n = 3 steers/pen) was calculated from: 600/seconds required for 10 flank movements. PS was determined from: 0 (not distressed) to 4.5 (severely distressed). Two separate heat events occurred and average THI was greater than 75 for 10-d of the 28-d period. A DFM×EHY interaction was noted for the proportion of steers categorized as PS 2.0 at 1100h on d21 ( P = 0.03) and RR on d21 at 1400h ( P = 0.02). Control steers had a greater proportion of PS 2.0 at 1100h on d21 compared with DFM or EHY steers ( P ≤ 0.05), while DFM×EHY steers did not differ from others (P ≥ 0.10). On d21 DFM×EHY steers had greater ( P < 0.05) RR compared with DFM steers, control and EHY steers did not differ from others ( P ≥ 0.10). DFM and EHY used alone or in combination had minimal effects on heat stress measures in steers fed RH in the NP under minimal heat stress conditions.